2017
DOI: 10.2169/internalmedicine.56.7563
|View full text |Cite
|
Sign up to set email alerts
|

The Type of Vascular Access and the Incidence of Mortality in Japanese Dialysis Patients

Abstract: Objective The National Kidney Foundation (NKF) Kidney Disease Outcome Quality Initiative (KDOQI) guidelines have recommended the use of arteriovenous fistula (AVF) at the initiation of dialysis. However, there are significant differences in the dialysis environments of Japan and the United States, and there are few people who receive hemodialysis via a central venous catheter (CVC) in Japan. The aim of the present study was to examine the association between the type of vascular access at the initiation of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
(20 reference statements)
3
24
1
1
Order By: Relevance
“…Rayner et al reported that 15-50% of patients undergoing dialysis were initiated using temporary catheters 29 . Some reports have described that emergent initiation using a short-term CVC is associated with high rates of www.nature.com/scientificreports/ mortality and hospitalization [20][21][22]30 . In this study, 47% of all patients experienced emergent initiation, which was not much different from that found in pre-existing studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rayner et al reported that 15-50% of patients undergoing dialysis were initiated using temporary catheters 29 . Some reports have described that emergent initiation using a short-term CVC is associated with high rates of www.nature.com/scientificreports/ mortality and hospitalization [20][21][22]30 . In this study, 47% of all patients experienced emergent initiation, which was not much different from that found in pre-existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are many problems associated with dialysis care such as too many cases of emergent dialysis that need to use a central venous catheter (CVC), life-prolonging dialysis, and early death after initiation of dialysis therapy. In particular, some studies report that the unplanned initiation of dialysis using a CVC is associated with mortality [20][21][22] . As this emergent initiation of dialysis increases mortality and costs, the challenge is to find ways of avoiding its use.…”
mentioning
confidence: 99%
“…Indeed, epidemiological observational studies using administrative databases show that hemodialysis with an AVF gives a better survival advantage over the use of central venous catheters. [33][34][35][36] However, this view has recently been challenged as the survival advantage of native AVF is more likely related to general better health of patients referred for AVF creation and who develop a functioning AVF. [37][38][39] While it could be proposed that AVF may have potential protective effects through reduction in blood pressure, AVF also bypasses part of the blood flow that is destined to organ perfusion, increases heart rate, myocardial contractility and stroke volume and cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…The tertiary option is a central dialysis catheter that is partly placed in a subcutaneous tunnel (tunneled dialysis catheter (TDC)). [3][4][5] The reason for creating autogenous AVFs is that observational studies show a lower incidence of post-operative complications and fewer endovascular and surgical revisions for AVF failure in comparison with AVGs. In addition, the use of TDCs results in a significantly higher morbidity and mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…The placement of a central dialysis catheter is mainly used in emergency situations and in chronic HD if VA by AVF or AVS is not plausible. [3][4][5] AVF is used more frequently, also in elderly patients, in Japan, while in Europe and United States often HD is initiated by the use of an AVS or TDC. 6 In addition, over time, more upper-arm AVF and AVG are placed especially in Europe and United States.…”
Section: Introductionmentioning
confidence: 99%